The Role of Parents in Improving the Creativity of Early Childhood Through Traditional West Java Games (Case Study in RA Al-Khoeriyah, Banyuresmi, Garut) - Ajat Rukajat; M Makbul (UPI Kampus Cibiru, 2022)
This research starts from the emergence of the problem why do more young children choose electronic games than traditional games, even though traditional games can increase children's creativity well if parents play a role. The type of research used in this research is qualitative research with a qualitative approach. case study, where researchers try to uncover and examine how the role of parents in increasing early childhood creativity through traditional games. The research used was based on consideration of specific or typical status situations and conditions, the data collection technique used was interviews and documentation. The findings in this study are that parents have a role in increasing children's creativity in a better direction, through the ucing sumut game it turns out that children's creativity becomes better and richer compared to other traditional games, oray-orayan games are traditional games that do not increase children's creativity. The increase in creativity that occurs in children aged 5 to 6 years and in girls is better. Forms of increasing creativity which include ideas, attitudes, and creation.